FÍSICO-QUÍMICA DA ÁGUA E CARACTERIZAÇÃO DOS SEDIMENTOS DE UMA MICRO-BACIA COSTEIRA DE MATA ATLÂNTICA COM MÚLTIPLOS USOS DO SOLO, JACUECANGA, ANGRA DOS REIS, RJ. - D'angelo, Raffaela Araujo (2011)
Changes in the original land use and cover due to human activities development and and launch of domestic sewage directly into rivers, are factors causing the reduction in water quality and sediments in aquatic ecosystems. The Jacuecanga river basin (Angra dos Reis, RJ) has been suffering with growing changes in land use, mainly by population growth and development of different industrial activities, which can lead to degradation of its water resources. This study proposes the characterization of organic matter present in the main channel of this river system, its tributaries and its estuary. We evaluated the physical-chemical and sediments molecular markers as molecular, elemental and isotopic compositions with the aim of understanding the influence of changes in the primary coverage of the ground on the input of terrigenous organic material for these aquatic systems. A total of five samples were obtained at 16 stations on the rivers Jacuecanga, Caputera and Vermelho rivers, contemplating the various climate conditions of the year and a rain event. Sampling of surface sediments were performed at 14 stations in the river and 15 at the bay. The station (RJ2) located downstream of Vila Caputera showed trends of eutrophication due to deforestation, soil exposure and disorderly urban occupation characterized by greater intake of carbon, nitrogen, BOD and SPM. In the estuarine zone, the density of the urban Vila Jacuecanga was related to high percentages of carbon and nitrogen, especially during rain events. Rainwater draining Transpetro Plant are discharged into the river at the end of the stretch of Jacuecanga freshwater and showed features alternating between the dry season with high conductivity, and the rainy season with high concentrations of SPM, but did not interfere relevantly in water quality of river Jacuecanga. Likewise, the side entrance of water coming from the stabilization pond and the waters of the Vermelho River with low oxygen and high content of organic material did not show significant changes in river. In the sediments of Jacuecanga river were observed the predominance of the sandy fraction demonstrating the intense hydrodynamics and lack of organic deposits along the basin. In the estuarine portion was recorded higher organic matter content with the identification of sources of vegetal remains and coprostanol from the greater urban density that occurs in the right margin. The sediments of bay located near the mouth of the river Jacuecanga and influenced by the plume showed higher levels of terrigenous organic matter quality (vegetal remains and effluents). Marine sediments, most distant from the river mouth, had lower levels of organic matter with phytoplankton characteristic. Sediments located in the zone of mixing water presented intermediate values. Fecal contamination was checked at the station nearest the river mouth and fecal influence in two nearby stations, but located outside the drainage channel of the Village of Jacuecanga belonging to neighboring watershed.